THE ALGORITHM OF SUPPLEMENTARY ARGUMENTS INCLUSION FOR INTERVAL MODELS STRUCTURAL IDENTIFICATION OF THE STATIC SYSTEMS - Dyvak, Mykola; Manzhula, Volodymyr (International Journal of Computing, 2014)
The problem of structural identification of static models of interval systems. Showing getting a unique solution for the problem of structural identification for different initial given structure models based on the complexity of the proposed algorithm sequential structures. An adaptive iterative procedure, which reduces the dependence of the result of structural identification of the magnitude interval error data.